2019
DOI: 10.1111/jnu.12467
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coping Strategies on Nurses’ Well‐Being and Practice

Abstract: Objectives:To examine the mechanisms of coping strategies on nurses' psychological well-being, practice environments and safety attitudes. Methods: A cross-sectional study design was used. Structural equation modeling was performed to analyze the results. Five hundred clinical nurses were randomly selected from a large group of 1,500 from a medical center with 1,350 beds in Taipei, Taiwan, from July to October 2015. Self-report questionnaires were administered to measure coping strategies (Brief COPE), psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 45 publications
(68 reference statements)
2
35
0
10
Order By: Relevance
“…Our results are consistent with those of previous studies (De Vibe et al, ; Park & Adler, ; Tavakolizadeh et al, ). The correlationship among PFC, EFC, and PWB is consistent with a recent study (Lee et al, ) in which researchers indicated that approach‐oriented coping similar to PFC was associated with improved PWB, whereas avoidant coping similar to EFC was a counterproductive coping style for PWB.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results are consistent with those of previous studies (De Vibe et al, ; Park & Adler, ; Tavakolizadeh et al, ). The correlationship among PFC, EFC, and PWB is consistent with a recent study (Lee et al, ) in which researchers indicated that approach‐oriented coping similar to PFC was associated with improved PWB, whereas avoidant coping similar to EFC was a counterproductive coping style for PWB.…”
Section: Discussionsupporting
confidence: 90%
“…For many decades, high nurse turnover rates have been a global phenomenon (Lee, Tzeng, & Chiang, ; Nursing Solutions Inc., ). The turnover rate of hospital nurses, especially new nurses, has been noted in academia and in clinical settings due to implications regarding patient safety and economic factors (Han, Choi, & Lee, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Above all, a good nursing practice environment could be regarded as a moderating variable, increasing staff's perceived professional benefits. For successful implementation, nursing administrators should implement effective strategies to promote a comfortable practice environment [6,53].…”
Section: Discussionmentioning
confidence: 99%
“…Today the more and the more researches evidence the relation between stress and various disorders and that stress has significant effect on psychological well-being and health. The relationship between coping strategies and well-being under stress (Yang, 2010) and the use of approach-oriented coping strategies is significantly predictive of positive psychological well-being (Lee et al, 2019). Stress management and coping strategies are essential for the balanced life.…”
Section: Introductionmentioning
confidence: 99%